Effect of Dietary Chromium Supplementation in Transition Calf: Effect on Insulin Sensitivity and Dynamics of Biomarkers of Rumen Development - Shivam Khare; kumar, Muneendra; Vinod Kumar; Raju Kushwaha; Shalini Vaswani; Avinash Kumar; Pankaj Kumar Shukla; Amit Kumar Jaiswal; Srishtipriya Prasad (Indian Journal of Animal Nutrition, 2025)
This 100-day transition phase study was started at 15 days of age and ended at 115 days of calves’ age. A total of 24 Hariana calves were randomly assigned into four groups (n = 6), i.e., without supplemental chromium (Cr) as control or 0.05 mg, 0.10 mg, and 0.15 mg Cr/kg BW0.75 groups. Treatment has no effect on the average daily gain (ADG) and body condition score (BCS). The dynamics of blood biomarkers were studied at 0, 30, 60, 70, 80, 84, 86, 87, 88, 89, 90, 95, and 100 days post-Cr supplementation. In the present study, plasma glucose, insulin, insulin: glucose ratio, and IRS-1 were used as biomarkers of insulin sensitivity while BHBA, NEFA and IGF-1 were used as biomarker of rumen development. Plasma glucose and insulin concentrations decreased (p < 0.05) with the advancement of age of calf and levels were lowest (p < 0.05) in the calves fed on a diet supplemented with highest Cr level (0.15 mg of Cr/kg BW0.75). However, insulin: glucose ratio was found to be greater (p < 0.05) in the calves receiving diet supplemented with Cr. Treatment, period and treatment × period interaction had a significant (p < 0.05) effect on plasma IRS-1 concentrations. Plasma IRS-1 concentration increased with the increase in supplementation level of Cr. A non significant effect of the treatment, period, and treatment × period interaction was observed on plasma BHBA and NEFA levels. However, a significant (p < 0.05) effect of treatment, period, and treatment × period interaction on plasma IGF-1 concentrations with greater (p < 0.05) plasma IGF-1 concentration in 0.15 mg of Cr/kg BW0.75 supplemented calves. Accordingly, as the level of Cr supplementation increased, plasma Cr concentration also increased and was noticed highest in the calves supplemented with 0.15 mg of Cr/kg BW0.75. In conclusion, the dietary supplementation of Cr helps in the smooth transitioning of calves from pre-ruminant to ruminant stage by improving insulin sensitivity and modulating biomarkers of rumen development.